Role of novel histone modifications in cancer - Shanmugam, M.; Arfuso, Frank; Arumugam, S.; Chinnathambi, A.; Jinsong, B.; Warrier, Sudha; Wang, L.; Kumar, A.; Ahn, K.; Sethi, G.; Lakshmanan, M. (Impact Journals LLC, 2018)
© Shanmugam et al. Oncogenesis is a multistep process mediated by a variety of factors including epigenetic modifications. Global epigenetic post-translational modifications have been detected in almost all cancers types. Epigenetic changes appear briefly and do not involve permanent changes to the primary DNA sequence. These epigenetic modifications occur in key oncogenes, tumor suppressor genes, and transcription factors, leading to cancer initiation and progression. The most commonly observed epigenetic changes include DNA methylation, histone lysine methylation and demethylation, histone lysine acetylation and deacetylation. However, there are several other novel post-translational modifications that have been observed in recent times such as neddylation, sumoylation, glycosylation, phosphorylation, poly- ADP ribosylation, ubiquitination as well as transcriptional regulation and these have been briefly discussed in this article. We have also highlighted the diverse epigenetic changes that occur during the process of tumorigenesis and described the role of histone modifications that can occur on tumor suppressor genes as well as oncogenes, which regulate tumorigenesis and can thus form the basis of novel strategies for cancer therapy.